Isolation and cytotoxic activity testing of compounds from Grewia bulot - Tý, Phạm Việt; Thảo, Châu Thị Thanh; Nhàn, Đặng Thị Thanh; Thắng, Lê Quốc; Bảo Nguyễn Chí (Hue University Journal of Science: Natural Science, 2024)
Three compounds, including β-amyrin (1), quercetin (2) and β-sitosterol (3), were isolated from the leaves of Grewia bulot. Their structures were elucidated by using infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) spectroscopy and by comparing them with spectroscopic data in the literature. The cytotoxic testing results of the isolated compounds against four tested cancer cell lines (MCF-7, Hep-G2, SK-LU-1, and KB) showed that β-amyrin had weak activity on three cell lines MCF-7, Hep-G2, and SK-LU-1 with IC50 values ranging from 72.3 to 96.15 µg·mL–1. This is the first time these compounds were isolated from Grewia bulot and evaluated for their cytotoxic activity.